Effect of exposure to particulate matter 2.5 on lung function performance of construction workers / Siti Aisyah Abdul Rahman - Abdul Rahman, Siti Aisyah (2018)
The aim of this study is to determine the concentration of PM2.5 emitted from construction activities which are masonry, plastering, and mixing of concrete and to evaluate the lung function performance by peak expiratory flow rate (PEFR) of the exposed construction workers. The concentration of PM2.5 was measured by using Dustrack. The sampling period is 8 hours per day for 6 days for each activity. Each activity demonstrate a different pattern and level of PM2.5 concentration. Based on result obtained, the masonry has the highest mean concentration of PM2.5 which is 79.98 µg/m³. Masonry and mixing of concrete just slightly different and both activities are exceed the standard limit. Meanwhile, the peak expiratory flow rate (PEFR) test was conducted by using peak flow meter. A total 80 participants were participated in PEFR test. Moreover, participants from plastering activity has the highest mean of PEFR which is 343.65 L/min. Masonry and mixing of concrete activity has a lower mean of PEFR with 329.26 L/min and 298.62 L/min respectively. Meanwhile, there is a significant negative correlation between age and PEFR of participants. Higher age group tend to have lower PEFR value. Lastly, the mean concentration of PM2.5 and PEFR has significant negative correlation. The higher the mean concentration of PM2.5, the lower the PEFR. The null hypothesis is failed to reject.